Pengaruh Kecerdasan Intelektual (Iq) Dan Religiusitas Terhadap Perilaku Etis Auditor Dengan Love Of Money Sebagai Variabel Intervening - Arindra Tri Hapsari; Dr. Novi Darmayanti, SE, MSA, Ak, CA.; Isnaini Anniswati Rosyida (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2022)
ABSTRACTThis study aims to determine how much influence intellectual intelligence (IQ) and religiosity have on the ethical behavior of auditors in the study of the Inspectorate of Bojonegoro Regency and the Inspectorate of Tuban Regency, and then how the love of money variable affects the second variable on the ethical behavior of auditors. The of data collection was done by using a questionnaire which was distributed to APIP and JFA Inspectorate The sample used in this study were 50 respondents with saturated sampling technique. The data obtained were processed with SPSS version 28. Based on the results of the study, it was concluded that partially intellectual intelligence and religiosity had a positive and significant effect on the ethical behaviour of auditors. Path analysis test results show that intellectual intelligence has no effect on ethical behavior through love of money as intervening variable and relgiosity variable affect auditor ethical behavior through love of money as an intervening variable. Â